Characterization of intron loss events in mammals - Coulombe-Huntington, Jasmin; Majewski, Jacek (Genome Research, 2007)
The exon/intron structure of eukaryotic genes differs extensively across species, but the mechanisms and relative rates of intron loss and gain are still poorly understood. Here, we used whole-genome sequence alignments of human, mouse, rat, and dog to perform a genome-wide analysis of intron loss and gain events in >17,000 mammalian genes. We found no evidence for intron gain and 122 cases of intron loss, most of which occurred within the rodent lineage. The majority (68%) of the deleted introns were extremely small (<150 bp), significantly smaller than average. The intron losses occurred almost exclusively within highly expressed, housekeeping genes, supporting the hypothesis that intron loss is mediated via germline recombination of genomic DNA with intronless cDNA. This study constitutes the largest scale analysis for intron dynamics in vertebrates to date and allows us to confirm and extend several hypotheses previously based on much smaller samples. Our results in mammals show that intron gain has not been a factor in the evolution of gene structure during the past 95 Myr and has likely been restricted to more ancient history.